Portugal : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper and Statistical Appendix examines Portugal's real convergence experience, and highlights the growth payoff of reform policies in determining the country's rapid growth during most of the past decade. The paper identifies potential areas for reform by examining developments in the unemployment-vacancy relationship since the early 1980s. The paper highlights that an issue for Portugal as a prospective European Monetary Union member is that of the strength of its financial links with Spain. The paper also examines such linkages as derived from daily data on short-term interest rates.